Insecticidal potential of seeds of Datura metel L., Abrus precatorius L., and Diploknema butyracea (Roxb.) H.J. Lam - Maharjan, E.; Wong, M. Y.; Upadhyay, S. K.; Joshi, T. Prasai; Panta, P.; Adhikari, R.; Joshi, D. R. (Forest Research and Training Centre, 2025)
The present study aimed to assess the insecticidal efficacy of methanol extracts of the seeds of three plants: Datura metel L., Abrus precatorius L., and Diploknema butyracea (Roxb.) H.J. Lam. The bioactive compounds in crude extracts were analyzed using Fourier Transform Infrared (FTIR) spectroscopy and Gas Chromatography-Mass Spectrometry (GC-MS). Insecticidal activities of different concentrations of extracts were evaluated against adults and the second instar larvae of Drosophila melanogaster by using ingestion and spraying methods. Among the three seeds, the extract of Datura metel L. at a concentration of 30 mg/mL consistently exhibited a higher mortality rate of 73.33±7.64% against adult insects while applying each method. However, all concentrations of the seed extracts exhibited lower mortality rates in larvae compared to adults of D. melanogaster. The qualitative phytochemical analysis of the seed extracts revealed the presence of detected alkaloids, phenols, flavonoids, carbohydrates, saponins, and tannins. FTIR analysis of the seeds revealed the presence of alcohols or phenols, alkanes, esters or ethers, amines, ketones, and nitro-compounds. GC-MS analysis identified a wide array of bioactive compounds. Abrus precatorius L. contained 1,2,3-benzenetriol, and 9-octadecenoic acid, methyl ester (E)-. Atropine, and scopolamine were abundantly detected in Datura metel L. Similarly, stigmasterol, 2,4,6-triaminoquinazoline, and brucine were identified in Diploknema butyracea (Roxb.) H.J. Lam. Since these GC-MS identified compounds are known for insecticidal properties, the seeds of all three plants particularly Datura metel L., can be a potential candidate for development as biopesticide against insect pests. Although field applications require further verification, our findings provide laboratory-based evidence supporting the potential of Nepalese indigenous plant-based biopesticides for reducing crop loss and enhancing food security.